Trade Finance in Crisis : Market Adjustment or Market Failure? - Chauffour, Jean-Pierre (2012)
As world leaders have agreed to massively support trade finance, this paper discusses the singularity of the issues related to trade finance in the context of the global economic crisis. Why should international trade finance be a particular issue of concern in the current circumstances? Are there specific market or government failures associated with trade finance that justify a special and differential treatment of the issue by policymakers? If so, what would then be the most appropriate policy instruments to address those concerns? The paper cautions against the notion of a large trade finance "gap," yet highlights the possible rationales and conditions for an effective intervention in support of trade finance.